Perceived quality of essential newborn care implementation among health facility deliveries in North Gondar Zone, Northwest Ethiopia: a cross-sectional study - Tadesse Guadu Delele; Gashaw Andargie Biks; Solomon Mekonnen Abebe; Zemene Tigabu Kebede (BMC, 2021)
Plain language summary Essential newborn care is a set of practices provided by healthcare workers and mothers to every newborn during delivery. Studies are scarce regarding the quality of newborn care implementation. Therefore, this study aimed to measure the magnitude and factors associated with essential newborn care implementation perceived quality among health facility deliveries in Northwest Ethiopia. A facility-based cross-sectional study design was employed to collect data from 370 randomly selected deliveries in 11 health facilities. A pre-tested interviewer-administered structured questionnaire was adopted from different kinds of literature and guidelines. A binary logistic regression model was fitted to assess the strength and significant level of the association at p-value < 0.05. The overall implementation perceived quality of essential newborn care was found to be 66.3%. The implementation perceived quality of cord care, breast-feeding and thermal care was 75.4, 72.2 and 66.3% respectively. Newborn immunization and vitamin K administration had the lowest implementation perceived quality i.e. 22.4 and 24.3% respectively. Friendly care during delivery (AOR = 5.1, 95% CI: 2.4, 11.0), partograph uses (AOR = 3.0, 95% CI: 1.1, 8.6), child immunization service readiness (AOR = 2.9, 95% CI: 1.5, 5.7), BEmEONC service readiness (AOR = 2.1, 95% CI: 1.2, 3.9) and facing no neonatal illness at all (AOR = 4.2, 95% CI: 1.6, 10.9) were significantly associated with good essential newborn care implementation qualities. The perceived quality of essential newborn care implementation was low in the study area. This is associated with poor readiness on BEmEONC and child immunization services, unfriendly care and not using partograph during delivery. Hence, availing the BEmEONC and child immunization service inputs, continuous training and motivation of healthcare workers for friendly care are vital for improving essential newborn care implementation perceived quality.